The investigation of relationships among sprint and jump performance with velocity parameters during propulsive phase of full back squat exercise - Erdal Arı; Hamit Cıhan; Ibrahim Can (Türk Spor ve Egzersiz Dergisi)
The basic purpose of this study was to investigate of the relationships with sprint and jump performance of velocity parameters during propulsive phase of full back squat exercise and to determine which variable was associated with which loading. For this purpose, thirty-two men amateur athletes (age: 20.4 ± 1.98 years; height: 179.3 ± 7.23 cm; weight: 73.5 ± 9.85 kg) who actively involved in sports and have a basic level of force participated in voluntarily to this study. In the study, one repetition maximum (1RM) full squat (SQ) strength test, vertical jump test, 5 meters and 30 meters sprint test were applied. The descriptive statistics and Pearson correlation analysis was used for statistical evaluation of datas. According to analysis results; it was obtained that mean velocity (MV), mean propulsive velocity (MPV) and peak velocity (PV) values during propulsive phase of full back squat exercise performed in different loads were decreased in parallel with load increase. In addition, it was obtained that there was no statistically a significant relationships between 5 meters sprint times and vertical jump performance with MV, MPV and PV values during propulsive phase of full back SQ exercise performed at different loads of 1RM (p gt; 0.05). Conversely, it was obtained that there was a mean level, negative and statistically significant relationship between 30 meters sprint times with MV during propulsive phase of full back SQ movement performed at 20 % and % 90 of 1RM load values (r = - .412; r =  - .399, p lt; 0.05, respectively) and PV values obtained at 40 % and 60 % of 1RM load values (r = - .402; r =  - .370, p lt; 0.05, respectively). Consequently, it was suggested that movement velocity is not an important component for performance parameters as 5 meter sprint and jumping height.